(untitled) (Nordic Journal of African Studies, 2009)
This paper discusses the syntactic distributions of aspect in the grammar of Yorùbá Àkókó. It considers the various Yorùbá Àkókó aspectual contrasts relative to the inception, duration or completion of an event. This is called Aspectual Structure. The paper describes the Yorùbá Àkókó aspectual structure in terms of Gazdar et al’s (1985) framework which is called the Generalised Phrase Structure Grammar (GPSG). The Yorùbá Àkókó aspectual structure distinguishes between the perfective and the imperfective; the imperfective is further subdivided. All the verbal elements and the occurrences of auxiliary which mark the perfective, imperfective (habitual, progressive) as well as the tonal alternations that occur in some elements in Yorùbá Àkókó, are completely different from that of the Standard Yorùbá. This paper does not regard the perfective as an “unmarked category” of the aspectual subcategories. This is so because in Yorùbá Àkókó the perfective does not become neutralized whenever it occurs with other aspect categories. Using the GPSG framework, the paper also accounts for some co-occurrence restrictions and the right orders of aspectual auxiliary verbs in Yorùbá Àkókó. The paper, in addition, describes the Yorùbá Àkókó negative markers and asserts that they are sometimes tied with aspect markings. This paper conclusively draws attention to issues on Yorùbá dialectology which would need further research.